Government strategies for the prevention of human trafficking for sexual and labor exploitation in the Amazonas region - River Chavez Santos; Yuri Reina Marín; Einstein Sánchez Bardales; Omer Cruz Caro; Angelica María Carrasco Rituay; Alex Javier Sánchez Pantaleón; Milena Torres Fernández (Cogent Social Sciences, 2024)
Human trafficking is a crime that has been affecting thousands of victims of both sexes and all ages around the world. That is why the study analyzes government strategies in the prevention of human trafficking for sexual and labor exploitation in the Amazonas region, Peru. Identifying that, in the Amazonas region, the problem of human trafficking manifests itself in remote and border areas, mainly in the province of Condorcanqui, where sexual exploitation of women and forced labor predominates, especially of boys, girls, and teenagers. The most common is "sponsorship", where people close to the victim deceive them by offering them work or study opportunities and then exploit them. This study suggests that there is more work to do in monitoring sex tourism, work modalities, boys and girls, and adolescents in vulnerable areas, and conditions of poverty, are some strategies to pay attention to prevent human trafficking.